Quality of coding of the final diagnoses of medical records and some related factors in a selected sample of hospitalsin Colombo district - Gamage, U.S.H (My University, 2002)
This study was under taken with the objective of assessing the quality of ICD coding and to identify some factors influencing. Out of all the hospitals in Colombo district (n=24), only TH and special hospitals were found to be having adequate physical facilities and human resource in medical record department for ICD cording. All the coders (n=31) in the hospitals of Colombo District were studied for socio demographic profile, coding practices and their attitudes towards coding. Of the coders, 29 per cent had confessed that they actually do not code and use alternative methods to prepare IMMR, and 25 per cent were having unfavorable attitudes towards coding. Training opportunities should be made available to the corders, in ICD -10 and other related subjects. Medical records departments should be adequately staffed and provided with necessary physical facilities. Efforts should be made to improve the familiarity of the medical officers with the WHO guidelines on recording diagnostic information for ICD coding. Training opportunities should be made available to the coders, in ICD-10 and other related subjects. Medical records department should be adequately staffed and provided with necessary physical facilities. Efforts should be made to improve the familiarity of the medical officers with the WHO guidelines on recording diagnostic information for ICD coding